A Neglected Narrative in the COVID-19 Pandemic: Epidemiological and Clinical Impacts of the COVID-19 Outbreak on Syphilis - Liu M; Zhou J; Lan Y; Zhang H; Wu M; Zhang X; Leng L; Mi X; Li J (Clinical, Cosmetic and Investigational Dermatology, 2023)
Mingjuan Liu,1– 3 Jia Zhou,1,2 Yining Lan,1,2 Hanlin Zhang,1,2 Mengyin Wu,1,2 Xinyi Zhang,4 Ling Leng,1,2 Xia Mi,5 Jun Li1,2 1Department of Dermatology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 2State Key Laboratory of Complex Severe and Rare Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 3 4+4 M.D. Program, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 4Departments of Internal Medicine and Cellular & Molecular Physiology, Yale School of Medicine, New Haven, CT, USA; 5Department of Dermatology, Strategic Support Force Medical Center, Beijing, People’s Republic of ChinaCorrespondence: Xia Mi; Jun Li, Tel +86-69156699, Email mixia501@163.com; lijun35@hotmail.comAbstract: The COVID-19 pandemic has profoundly changed our lives. While healthcare resources were redistributed and mobilized to focus on dealing with the COVID-19 crisis, there have been unmet medical needs of patients with other diseases such as syphilis, weaving an integral but neglected component of the pandemic story. In different countries, the epidemiology of newly reported syphilis underwent diverse changes during the COVID-19 pandemic. Asymptomatic cases experienced the largest decline in number. From the perspective of transmission, on one hand, the implementation of lockdown measures led to a higher degree of abstinence and sex distancing in many countries, thereby reducing the transmission of syphilis. On the other hand, vertical transmission was reported to have increased significantly during COVID-19. Meanwhile, the volume of STI clinic capacity declined, and STI staff were redeployed to facilitate the contact tracing of COVID-19. As a result, many STI centers converted traditional in-person clinical services to telemedicine and self-testing. However, syphilis testing and clinical treatment cannot fully adapt to this conversion. In syphilis diagnosis, COVID-19 infection and vaccination were reported to cause false positivity in syphilis serological tests. Diverse cutaneous manifestations of COVID-19 could resemble the skin lesions in syphilis patients, requiring differential diagnosis from clinicians. As for the post-pandemic years, consequent to service interruptions and diagnosis delays, a surge in the number of confirmed cases of syphilis is expected. The COVID-19 pandemic has also been a meaningful lesson for the control and prevention of infectious diseases. The experience in combating COVID-19 has underscored the importance of maintaining a robust and well-supported medical system for the provision of sexual health services and better healthcare equality even during eras of crisis, not least for syphilis patients.Keywords: COVID-19, syphilis, sexual behavior, STD prevention